2004
DOI: 10.1097/01.sla.0000143250.48265.d6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Laparoscopic Versus Open Pyloromyotomy

Abstract: OP is associated with fewer complications and higher efficacy. Recovery time appears significantly shorter following LP. A prospective randomized controlled trial is warranted to fully investigate these and other outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 15 publications
5
78
4
2
Order By: Relevance
“…Formation of scar retraction appeared to be related to the existence of a previous wound infection, although this association was statistically not quite significant. Wound infection rate of present series was 5.8%, which well compares with that of current average reported by other series for both circumumbilical and laparoscopic pyloromyotomies [8,[12][13][14]. Indeed, the literature suggests that patients operated on using a circumumbilical incision have an increased risk for wound infection development.…”
Section: Discussionsupporting
confidence: 87%
“…Formation of scar retraction appeared to be related to the existence of a previous wound infection, although this association was statistically not quite significant. Wound infection rate of present series was 5.8%, which well compares with that of current average reported by other series for both circumumbilical and laparoscopic pyloromyotomies [8,[12][13][14]. Indeed, the literature suggests that patients operated on using a circumumbilical incision have an increased risk for wound infection development.…”
Section: Discussionsupporting
confidence: 87%
“…Hall et al [20] in 2004 performed a meta-analysis of studies comparing open and LP and concluded that the open approach is associated with fewer complications and higher efficacy but exalt the significantly shorter recovery time after LP. The appearance of a higher complication rate in LP may be justified by the learning curve as much as if the operation is performed by a general surgery resident [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…However, in 2004 a meta-analysis of reported studies by Hall et al [17] was unable to show a clear benefit of laparoscopic approach over the open technique. In a recent meta-analysis of the data from five level 1 studies and one level 2 study, Sola and Neville [9] concluded that the laparoscopic approach yields a significantly reduced rate of total complications.…”
Section: Discussionmentioning
confidence: 99%